FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SISWA KELAS VIII TAHUN AJARAN 2013-2014 DI SMP MUHAMMADIYAH 6 KOTA PADANG - Prasetyo, Heru; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACK             The purpose of this study was to 1 ) determine the factors influencing parental education student learning outcomes , 2 ) Knowing parental income factors affecting student learning outcomes , 3 ) determine factors influencing parental concern student learning outcomes , and 4 ) Knowing the factors parental education , parental income and parental concern collectively. learning outcomes eighth grade school year 2013/2014 in SMP Muhammadiyah 6 Padang.This type of research is classified as a type of descriptive research Correltional. The population was eighth grade students at SMP Muhammadiyah 6 Padang totaling 96 people . The sample of respondents was taken by total sampling where the entire population is a subject of research . A total of 66 respondents and VIII2 VIII1 class . Because VIII3 class used to test insrumen research , the authors chose VIII1 and VIII2 as research samples.The results of the study the factors that affect student learning outcomes in class VIII SMP Muhammadiyah 6 Padang produce findings as follows : For the effect of parental education on student learning outcomes , t count > t table , ie 18,285 > 1.99834 and significance value 0.000 < α 0.05 . This suggests that education ( X1 ) significant and positive impact on student learning outcomes ( Y ) So the first hypothesis in this study the effect of parental income accepting. to on student learning outcomes , t count > t table , ie 2.165 > 1.99834 and significance value 0.034 < α 0.05 . This suggests that income ( X2 ) significant and positive impact on student learning outcomes ( Y ) So the first hypothesis in this study accepting. and to influence parental supervision of student learning outcomes , t count > t table , namely 2472 > 1.99834 and 0.016 significance value < α 0.05 . This suggests that parental concern ( X3 ) significant and positive impact on student learning outcomes ( Y ) So the first hypothesis in this study received .